Cross-Species Boundaries and Human Rights: Legal and Ethical Reflections on Xenotransplantation - Baldussu, Sara (Bioethica, 2025)
Xenotransplantation, i.e. the transplantation of cells, tissues, or organs derived from animals into humans—stands at the forefront of biomedical innovation, offering a promising solution to the persistent shortage of human donor organs. As this field advances rapidly, it simultaneously raises complex scientific, ethical, and legal challenges that demand careful consideration. The responsibility to safeguard animal welfare while ensuring human health protection is paramount, particularly given the zoonotic risks inherent in xenotransplantation research. Preclinical studies must rigorously address the potential for transmission of infectious agents from animals to humans, requiring robust risk assessment and management strategies that protect not only individual patients but also public health at large. Balancing these concerns with the imperative to develop life-saving therapies underscores the vital role of scientific responsibility. Ethical questions surrounding xenotransplantation go beyond traditional biomedical concerns, probing deeply into the boundaries between species and what it means to be human. The creation and use of chimeras and hybrids challenge established concepts of identity, raising questions about the moral status of these entities and the ethical limits of scientific intervention. Patient rights remain central in this discourse, especially regarding informed consent, compassionate use of experimental treatments, and the equitable distribution of scarce organs. These issues compel ongoing reflection on autonomy, justice, and societal values, highlighting the need for ethical frameworks that can guide clinical practice and research in this emerging field. At the same time, xenotransplantation operates within a diverse and evolving global legal landscape. Regulatory frameworks vary considerably across countries, reflecting different cultural, ethical, and political priorities. International organizations such as the International Xenotransplantation Association (IXA) and the World Health Organization (WHO) play critical roles in shaping policies, offering guidance, and promoting harmonization to facilitate responsible development and safe clinical application. Navigating this complex regulatory environment is essential for researchers and clinicians, who must comply with multifaceted requirements to ensure the ethical conduct of clinical trials and patient safety. This article integrates scientific, ethical, and legal perspectives to provide a comprehensive overview of the current state and future prospects of xenotransplantation. It emphasizes the importance of an interdisciplinary approach that promotes innovation while rigorously addressing risks and respecting both animal welfare and human dignity. By fostering collaboration among scientists, ethicists, policymakers, and healthcare providers, the xenotransplantation field can advance responsibly, ultimately transforming the landscape of transplantation medicine and offering new hope to patients facing organ failure worldwide.